If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 40 = 15x + -42 Reorder the terms: 40 + 6x = 15x + -42 Reorder the terms: 40 + 6x = -42 + 15x Solving 40 + 6x = -42 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 40 + 6x + -15x = -42 + 15x + -15x Combine like terms: 6x + -15x = -9x 40 + -9x = -42 + 15x + -15x Combine like terms: 15x + -15x = 0 40 + -9x = -42 + 0 40 + -9x = -42 Add '-40' to each side of the equation. 40 + -40 + -9x = -42 + -40 Combine like terms: 40 + -40 = 0 0 + -9x = -42 + -40 -9x = -42 + -40 Combine like terms: -42 + -40 = -82 -9x = -82 Divide each side by '-9'. x = 9.111111111 Simplifying x = 9.111111111
| 2x^2-7=3x+4 | | -2y*2=0 | | (a)5w+3=4w+9 | | k+hj=6 | | 3-6x=11x-8x | | -2y*-y=0 | | 6a^2-30a+24= | | 2.7x+2.8=19 | | -17=3+5 | | 9x-12+2x=11x+6 | | d-2.94=1.36 | | 2(3x+4)-3=6x+5 | | -5+9=21 | | 3m-10=24m-5 | | x/18+x/3 | | 8(y+6)+y=4(y+5)+2 | | 1/31/2x/3 | | -4(3x-4)+1=-12x+17 | | 5x+4=12+5x | | 2x-3+4x-8=13 | | 5*29= | | 7x-8y=64 | | 11*15= | | 2(x-4)(x-3)=x-13 | | 9x+6=9(x-3) | | X+4/3=x-8/5 | | X/4-3=-4 | | -8-3+6*2= | | 3z=14-29 | | 3(3m-2)+10=3(m-4)-3 | | 23x-7-14x+4=25x-4-16x+12 | | (5a-2)(7a+3)=0 |